2017
DOI: 10.5897/ajmr2016.8226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tobacco tar on Staphylococcus aureus and Candida albicans biofilm formation

Abstract: Twenty compounds were determined in the tar of cigarette smoke. The tar was obtained using tobacco filters and then analyzed by liquid chromatography-mass spectrometry (LC-MS). Tobacco tar expressed marked decrease in the susceptibility of Staphylococcus aureus to penicillin, tetracycline and amoxicillin/clavulanic antibiotics and showed marked decrease in susceptibility of Candida albicans to the tested antifungals except for clotrimazole and ketoconazole. Tobacco tar decreased the permeability of the tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Most of the isolated bacteria are included among the potential causes of bacterial pneumonia and infections in lower respiratory tract [11–13]. Recently, Mahmoud et al [14] reported that tobacco tar increases microbial hydrophobicity that leads to the increase of microbial adherence to epithelial cells and their colonization, which is considered the first step in developing invasive infections. Interestingly, this study has shown that Klebsiella oxytoca and Aerococcus viridians contaminated water bowl and mouthpiece of the same samples in Hafar Al-Batin and Kocuria rhizophila in Al-Ghat and Riyadh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the isolated bacteria are included among the potential causes of bacterial pneumonia and infections in lower respiratory tract [11–13]. Recently, Mahmoud et al [14] reported that tobacco tar increases microbial hydrophobicity that leads to the increase of microbial adherence to epithelial cells and their colonization, which is considered the first step in developing invasive infections. Interestingly, this study has shown that Klebsiella oxytoca and Aerococcus viridians contaminated water bowl and mouthpiece of the same samples in Hafar Al-Batin and Kocuria rhizophila in Al-Ghat and Riyadh.…”
Section: Discussionmentioning
confidence: 99%
“…Water bowl can act as a good environment for the growth of bacterial pathogens and also the microbes can acquire/develop drug resistance capability [14]. Smoke which is drawn through water can transmit bacterial pathogens to the smokers and cause serious health effects.…”
Section: Discussionmentioning
confidence: 99%